Działania o charakterze ekspresyjnym w perspektywie kapitału społecznego i ich znaczenie dla osób niepełnosprawnych - Masłyk, Tomasz (Instytut Socjologii Uniwersytetu Wrocławskiego, 2019)
The aim of the article is to discuss the role of expressive actions undertaken by people with disabilities in the perspective of social capital. Disability and its impact on the lives of people affected by it is most often considered in reference to the premises of either the bio-psychosocial model or the social one. The former, essentialist approach emphasises the significance of perceptual-motor dysfunctions that constitute a significant barrier to everyday activities undertaken by people with disabilities. The latter, constructivist approach puts emphasis on the necessity to eliminate external barriers: infrastructural, institutional, but also, and above all, those connected with mentality and awareness as they determine the way in which disability is defined and in which people affected by it are perceived by society. Regardless of the direction adopted, in both approaches emotions will play a key role in overcoming limitations (internal or external barriers). They are the basis for expressive actions that, from the perspective of social capital, facilitate the protection of resources possessed by an individual: physical health, mental health, and broadly understood quality of life. In order to achieve these goals, it is necessary to obtain support from the closest people in one’s life, namely family members and friends.
Keywords: social capital; expressive actions; instrumental actions; disabilities